T Technology Acceptance by University Teachers: A Demographic Analysis (European journal of volunteering and community-based projects, 2020)
Teaching processes have been evolved over centuries by adopting new approaches, methods, tools, and technologies. Teachers must carefully use, evaluate, and adopt the changes to utilize these technologies for teaching. The prime focus of this study was to explore technology acceptance by university academics and to analyze it with demographic characteristics. A mixed-method approach using sequential explanatory design was employed for the collection of data. The population of the study was comprised of university teachers around Pakistan.  A sample of 300 teachers was selected by employing proportionate stratified random sampling and 20 teachers were selected for the conduct of interviews. A five-point Likert scale questionnaire was developed for quantitative data collection. Validity was ensured through experts’ evaluation and pilot testing. Internal consistency and reliability of questionnaire items was checked through Cronbach’s alpha and found 0.83. Researcher himself visited the target audience for data collection. Data were analyzed through SPSS with arithmetic means, standard deviation, ANOVA, t-test, and posthoc multiple comparisons. Salient findings revealed that male teachers were significantly better in technology acceptance than their female counterparts; a significant and strong positive relationship was observed between technology acceptance and demographic characteristics of teachers. Technology Acceptance by university teachers was significantly less. It was recommended that female teachers must be imparted training regarding the effective use of technology and customized training must be conducted to enhance technology usage at the university level.
Keywords: Educational Technology; Acceptance; Adoption; Higher Education; Academics